Insights and future directions: Applying the One Health approach in international agricultural research for development to address food systems challenges - Hung Nguyen-Viet; Lam, Steven; Alonso, Silvia; Unger, Fred; Moodley, Arshnee; Bett, Bernard K.; Fèvre, Eric M.; Knight-Jones, Theodore J.D.; Mor, Siobhan M.; Ha Thi Thanh Nguyen; Grace, Delia (Elsevier, 2025)
For more than 15 years, the International Livestock Research Institute (ILRI) has been striving to understand and address One Health challenges at the intersection of livestock, humans, and the environment. We present an overview of ILRI One Health projects implemented with partners across Asia and Africa, reflecting on key learnings and future directions for One Health research and food systems transformation. Drawing on a review of peer-reviewed and grey literature, we analyzed processes and outcomes of ILRI-led and supported initiatives using a realist evaluation framework (context, mechanisms, outcomes), and present insights within select One Health topic areas such as zoonoses, food safety, antimicrobial resistance. Our findings emphasize the need for stronger cross-sectoral collaboration, greater engagement with policymakers to translate research findings into actionable strategies, and the development of adaptable and context-specific interventions.